2016
DOI: 10.1111/jphp.12573
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in Ehrlich ascites tumour cells via p53 activation by a novel small-molecule MDM2 inhibitor – LQFM030

Abstract: These results suggest that the small-molecule p53 activator LQFM030 (2) has the potential for further development as a novel cancer therapeutic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…( 2015 ) and Mota et al. ( 2016 ), respectively. After treatment, K562 cells (1 × 10 6 cells/mL) were harvested by centrifugation, washed with cold PBS and resuspended with BD Cytofix/Cytoperm™ solution for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 94%
“…( 2015 ) and Mota et al. ( 2016 ), respectively. After treatment, K562 cells (1 × 10 6 cells/mL) were harvested by centrifugation, washed with cold PBS and resuspended with BD Cytofix/Cytoperm™ solution for 20 min at 4 °C.…”
Section: Methodsmentioning
confidence: 94%
“…However, although known to significantly reduce ascites volume, none of these agents improved OS in clinical trials 36 . Regarding MDM2 inhibitors, previous studies reported that LQFM030 shows antitumor effects and an inhibitory effect on ascites production on Ehrlich ascites tumor cells derived from breast cancer 37,38 . Although the genetic and biological characteristics of CCCs are becoming clear, no single specific inhibitor has been shown to be sufficiently effective.…”
Section: Discussionmentioning
confidence: 99%